Local ecological knowledge for water management: a feasible solution through ecosystem services in high-Andean mountains - Flores Marquez, Ricardo (2026)
Introduction: Mountain ecosystems are particularly sensitive to the impacts of climate change, which, in turn, affect the wellbeing of local populations. In this context, the sustainable use of ecosystem services is crucial to supporting the social and economic welfare of Andean communities in South America. The development of local ecological knowledge has facilitated both environmental adaptation and strengthened environmental awareness. Particularly, the qocha, an ancestral water-related agricultural technology, provides hydro-social value, and represents a local climate-change adaptation measure, however their ecosystem services valuation has not been integrally performed. Thus, we aimed to map and assess the perceived services associated with Yuyuchaqocha, a small reservoir managed by a high-Andean community characterized by pronounced economic poverty. Methods: The methodology included semi-structured interviews with key informants, participatory mapping, and field observation. The participatory process involved the community, municipal, and technical stakeholders operating within the study area. The economic valuation was done by contingent valuation, market prices, and travel cost methods. Results: The results revealed that local inhabitants recognized 10 ecosystem services (five provisioning services and five cultural services), primarily concentrated along its shores. The total local perceived value of these services was estimated at USD 10,104.97, benefiting the rural communities of Huanupampa and Totos. Among the cultural services, those related to community organization, species conservation, and the pagapu celebration had the highest economic values. Discussions: Disseminating the results at various organizational levels would foster the integration of the local worldview into management plans, contributing to their legitimacy and sustainability, and promoting the involvement of institutions engaged in the intervention of mountain water socio-ecosystems. In this regard, integrating local ecological knowledge with ecosystem services valuation can be replicated or adapted in other regions.